CYBORG AND HYBRIDE GENDER UTOPIA IN SERBIAN CULTURE OF XXI CENTURY - Rosić, Tatjana (Porównania, 2015)
This paper analyses the status and place of the feminist and postmodern utopia of multiple identities in Serbian culture. Starting from a definition of cyborg as an utopian concept of the feminist thinking, given by Dona Haraway, the paper explores possible utopian aspects of the syntagma woman-writer that are based on constant change of gender identities and roles that the syntagma implies. The figure of female authorship in the context of neo-conservative spirit of the Serbian cultural market in transition is more than ever connected to the understand-ing and evaluation of the traditional concept and quality of "the feminine". The figure of female authorship in Serbian culture is also based on flirting with different feminist strategies of repre-senting, whether they ridicule or apparently support it. All this points to an urgent need of form-ing a serious stand about the studies of gender in this country and in the region.